2011
DOI: 10.1016/j.biologicals.2011.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Clinical programs in the development of similar biotherapeutic products: Rationale and general principles

Abstract: Similar biotherapeutic products (SBPs) or biosimilars are biologics developed by pharmaceutical manufacturers to match originator biologics that have been on the market for a long time and lost their exclusivity (patent and market protection). The recently issued WHO guidelines on evaluation of SBPs provide clear guidance for manufacturers and regulators on how to develop and gain approval for these products. The present contribution illustrates the rationale for and general principles of the clinical programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 8 publications
0
22
0
Order By: Relevance
“…Sandoz's clinical program consisted of PK/PD studies with healthy volunteers and a single-arm Phase III study. 19 Eurofarma performed stand-alone toxicological tests in animals. This decision was based on four main reasons: 1) the absence of significant toxicity described for the reference product; 2) existing knowledge of the clinical safety of the reference product present in the market for >20 years; 3) the desire to reduce animal usage; and 4) clinical safety in humans was planned in a comparative study and would result in more meaningful data for toxicity assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Sandoz's clinical program consisted of PK/PD studies with healthy volunteers and a single-arm Phase III study. 19 Eurofarma performed stand-alone toxicological tests in animals. This decision was based on four main reasons: 1) the absence of significant toxicity described for the reference product; 2) existing knowledge of the clinical safety of the reference product present in the market for >20 years; 3) the desire to reduce animal usage; and 4) clinical safety in humans was planned in a comparative study and would result in more meaningful data for toxicity assessment.…”
Section: Resultsmentioning
confidence: 99%
“…We checked mean levels of FVII before and after administration of the 2 rFVIIa preparations to prove FVII: C level was comparably increased. 6,38 In the previous studies, the rate of reported adverse events was 1% to 10%, [50][51][52][53][54][55][56][57][58][59][60] and the most of adverse events had been headache, rashes, hypertension, and rarely thrombosis. We did not encounter any thrombosis in either treatment groups.…”
Section: Discussionmentioning
confidence: 98%
“…[50][51][52] The primary reason for production of biosimilar drugs is reduction in the overall health care cost to design better comprehensive management and closing the gap between the poor and developed countries. [52][53] Double-blind, comparative clinical trials were designed for biosimilar rFVIIa (Aryoseven) in terms of clinical efficacy and noninferiority to Novoseven. This study showed increased FVII levels and clinical efficacy in the control of the bleeding episodes in patients with hemophilia A with inhibitor for both the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The first biosimilar erythropoietin-␣ in Europe proved to be equivalent with originator in clinical studies in terms of influencing the level of hemoglobin, moreover, no neutralizing antibody production was detected [81]. In the same way, clinical studies verified comparable efficacy and safety of biosimilars of human G-CSF (filgrastim), growth hormone and erythropoietin-␣ developed by Sandoz [82]. During the development of the growth hormone (Omnitrope ® ), anti-growth hormone Abs developed in 60% of patients in clinical studies due to excess host cell protein contamination.…”
Section: Immunogenicitymentioning
confidence: 88%